Tinjauan Kinerja Simpang Empat Bersinyal Menggunakan Program KAJI dan SIDRA (Studi Kasus: Simpang Pasar Moodu, Gorontalo) - Arsyad, A.W.; Kadir, Y.; Desei, F.L. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2022)
The Moodu Market intersection is a signalized intersection formed by the convergence of Jalan Sultan Botutihe-Jalan Matolodula and Jalan Prof Dr. H. Aloei Saboe. This intersection is one of the accesses to the Aloei Saboe Hospital, Fourth Campus of the State University of Gorontalo, offices in Bone Bolango Regency, and close to Moodu market. Large traffic flows that pass through this intersection causes congestion. The purpose of this research was to analyze the permormance of the intersection to determine the level of service at the intersection. The analytical method used to determine the performance of the intersection was conducted using the KAJI and SIDRA programs. Observations were conducted in three days (Monday, 22 March 2021; Thursday, 25 March 2021; and Sunday, 28 March 2021) starting att 06.00-18.00 WITA. The data used in the analysis included the intersection’s geometry, signal time, traffic volume, side barrier, cruise speed, pedestrian, and the population of Gorontalo City. The data was processed to find the values used to determine the performance of the intersection. Based on the results of analysis using the KAJI program, the average delay was 16.73 seconds for the north approach (Jalan Prof. Dr. H. Aloei Saboe), 12.75 seconds for the south approach (Jalan Matolodula), 25.86 seconds for the east approach (Jalan Sultan Botutihe), and 52.67 secinds for the west approach (Jalan Sultan Botutihe). Meanwhile, the results of the analysis using the SIDRA program showed that the average delay was 64.4 seconds for the north approach (Jalan Prof. Dr. H. Aloei Saboe), 13.1 seconds for the south approach (Jalan Matolodula), 42.0 seconds for the east approach (Jalan Sultan Botutihe), and 13.3 seconds the west approach (Jalan Sultan Botutihe). The average delay of the intersection based on the KAJI program was 32.11 seconds where its Level of Service was D while the average delay of the intersection based on the SIDRA program was 36.8 secinds whereas its Level of Service was D. The average percentage difference in the intersection delay using the KAJI and SIDRA Program was 12.75%.